Central projections of nociceptive input originating from the low back and limb muscle in rats - Hoheisel, Ulrich; Treede, Rolf-Detlef; Mense, Siegfried; Taguchi, Toru (Scientific reports, 2025)
Since clinical features of chronic muscle pain originating from the low back and limbs are different (higher prevalence and broader/duller sensation of low back muscle pain than limb muscle pain), spinal and/or supraspinal projection of nociceptive information could differ between the two muscles. We tested this hypothesis using c-Fos immunohistochemistry combined with retrograde-labeling of dorsal horn (DH) neurons projecting to ventrolateral periaqueductal grey (vlPAG) or ventral posterolateral nucleus of the thalamus (VPL) by fluorogold (FG) injections into the vlPAG or VPL. C-Fos expression in the DH was induced by injecting 5% formalin into the multifidus (MF, low back) or gastrocnemius-soleus (GS, limb) muscle. A double-labeled DH neuron showing both c-Fos-immunoreactive nucleus and retrogradely transported FG in the cytoplasm was considered as a nociceptive projection neuron. Consistent with DH somatotopy for proximal vs. distal cutaneous inputs, DH neurons with MF input were located in the most lateral area of laminae I − II (segments Th12 − L5), while those with GS input were located in the middle area of laminae I − II (L3 − L5). DH neurons projecting to the vlPAG were located in superficial DH, while those projecting to VPL were located in deep DH. Supraspinal projection derived from more spinal segments for MF input than for GS input. These data suggest that nociceptive input from low back muscles is integrated more in craniocaudal direction than for limb muscles, and that these signals are then forwarded to both PAG and thalamus and contribute to the different nature of muscle pain arising from the low back and limbs.